2018
DOI: 10.1002/pbc.27461
|View full text |Cite
|
Sign up to set email alerts
|

Fetal programming and Wilms tumor

Abstract: Background: The ‘fetal programming’ hypothesis has been evaluated in many adult diseases including cancer, but not for Wilms tumor. Wilms tumor has been related to high birthweight but little is known about other growth metrics such as a baby’s birth length, ponderal index, or placenta size, which can shed additional light on growth patterns. Methods: Cases of Wilms tumor (N=217) were taken from the Danish Cancer Registry, and controls (N=4,340) were randomly selected from the Population Register and matched… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 48 publications
(145 reference statements)
0
9
0
1
Order By: Relevance
“…Associations between pediatric cancers and parity have been attributed to increased risk of infectious conditions from having older siblings, or alternatively, variation in hormone levels between first and subsequent pregnancies . Furthermore, second‐born and subsequent babies have higher birth weights than first‐borns perhaps due to pregnancy‐induced uterine vascular remodeling leading to increased placental size in second pregnancies, and placenta size may also predict risk of some pediatric cancers …”
Section: Commentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Associations between pediatric cancers and parity have been attributed to increased risk of infectious conditions from having older siblings, or alternatively, variation in hormone levels between first and subsequent pregnancies . Furthermore, second‐born and subsequent babies have higher birth weights than first‐borns perhaps due to pregnancy‐induced uterine vascular remodeling leading to increased placental size in second pregnancies, and placenta size may also predict risk of some pediatric cancers …”
Section: Commentsmentioning
confidence: 99%
“…46 Furthermore, second-born and subsequent babies have higher birth weights than first-borns perhaps due to pregnancy-induced uterine vascular remodeling leading to increased placental size in second pregnancies, 47 and placenta size may also predict risk of some pediatric cancers. 48 Increased risk for ALL was seen with Cesarean section birth, although records did not allow us to determine the type of Cesarean (planned or emergency). Associations were previously reported with prelabor Cesarean delivery, 49 with the hypothesis that the elevated cortisol levels which occur with labor may eliminate preleukemic and leukemic cells (the "adrenal hypothesis" 50 ).…”
mentioning
confidence: 99%
“…O diagnóstico pré-operatório do nefroblastoma em adultos é difícil porque não há achados radiográficos específicos que permitam diferenciá-lo dos tumores renais adultos mais comuns. Histopatologicamente, não há diferença entre o tumor de Wilms em adultos e crianças (HECK, 2019;HUSZNO et al, 2013).…”
Section: Resultsunclassified
“…One SR (81), two cohort studies (82,83), and 12 casecontrol studies (51,78,80,(84)(85)(86)(87)(88)(89)(90)(91)(92) reported on Wilm's tumor in childhood. The SR being of medium quality reported an increased risk for Wilm's tumor if birth weight >4,000 g as well as for LGA [OR 1.36 (95% CI 1.12-1.64) and OR 1.51 (95% CI 1.25-1.83)] (81).…”
Section: Wilm's Tumormentioning
confidence: 99%